"Are Fans in the Stands an Afterthought?": Sports Events, Decision-Aid Technologies, and the Television Match Official in Rugby Union. (December 2021) - Stoney, Emma; Fletcher, Thomas
The intense commodification, commercialisation, mediatisation, globalisation, and digitalisation of sport in the past three decades have resulted in sporting organisations and governing bodies becoming inextricably tied to the global media industry and corporate economy. A result of this mediatisation, coupled with technological advancement, has been the introduction of decision-aid technologies in sport. Existing literature on decision-aid technologies has generally focused on the technologies themselves. Here, we focus on decision-aid technology use and its impact on event experience. This article examines fan attitudes towards the use of the Television Match Official (TMO) in rugby union in relation to the event experience. We present data from a global online questionnaire ( n = 194) and 11 semi-structured interviews with fans, representatives from rugby's governing bodies, two TMOs, and a television producer. Data show an inconsistency in how TMO decisions are relayed to match crowds, which had an impact on events experience. The data also reveal how heavily reliant the TMO system is on broadcasters. Fans were generally in favour of TMO use, but they did want to be better informed when it came to TMO referrals and decisions. Indeed, fans said improvements to TMO decision delivery in stadia, specifically having audio of referee/TMO discussions/decisions relayed over the stadium PA system and/or captions providing explanations and decisions on TMO referrals, would mostly improve their event experience.